2019
DOI: 10.1021/acs.chemmater.9b01337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surface Roughness on Light-Absorber Orientation in an Organic Photovoltaic Film

Abstract: Atomistic nonequilibrium molecular dynamics simulations have been used to model the orientation of a side-chain substituted dicyanovinyl oligothiophene, DCV4T-Et2, in thin films formed by vacuum deposition as used in organic photovoltaics. The orientation of the DCV4T-Et2 molecules was analyzed in neat layers deposited onto smooth or rough C60 substrates. The average angle between the long axis of DCV4T-Et2 and the horizontal was 21 ± 1° in the layer deposited on smooth C60, in agreement with experimental meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…45 Furthermore, changes in surface roughness can modify the orientation of the active layers molecule, which can increase or decrease the performance. 46 Since multiple effect are at work simultaneously it is hard to say whether the large decrease in surface roughness is beneficial, although the comparable performance between the VO-AP and VO-250, despite the higher roughness in the later case, probably indicates that any improvement are captured by the roughly halving of surface roughness due to VO-250 and any subsequent reduction offer little benefit.…”
Section: Discussionmentioning
confidence: 99%
“…45 Furthermore, changes in surface roughness can modify the orientation of the active layers molecule, which can increase or decrease the performance. 46 Since multiple effect are at work simultaneously it is hard to say whether the large decrease in surface roughness is beneficial, although the comparable performance between the VO-AP and VO-250, despite the higher roughness in the later case, probably indicates that any improvement are captured by the roughly halving of surface roughness due to VO-250 and any subsequent reduction offer little benefit.…”
Section: Discussionmentioning
confidence: 99%
“…20 Subsequent studies utilized elements of the PyThinFilm package to perform vacuum deposition simulations of both OLED and OSC thin films. These include: (I) Lee et al 2017 44 who investigated the transition dipole distribution of OLED emitter molecules, (II) Lee et al 2018 30 who reported an analysis of the morphology of a low donor concentration OSC bulk heterojunction film, (III) Lee et al 2019 35 who described a comparison of smooth and rough substrate morphology on molecular orientation within a neat OSC film, (IV) Gao et al 2020 5 who demonstrated that the charge-transport and photophysical properties were directly related to morphological features observed at 5 different blend ratios within 34 nm × 34 nm OLED films comprising over 14 000 molecules, and finally, (V) Sanderson et al 2021 45 who showed that the host−guest blend morphologies could be used to investigate exciton transport in an OLED thin film using kinetic Monte Carlo simulations.…”
Section: ■ Applicationsmentioning
confidence: 99%
“…In this work, we present a computational toolkit (PyThin-Film) that was developed to facilitate the simulation studies performed by Tonneléet al, 20 Lee et al, 35 Lee et al, 21 and Sanderson et al 34 PyThinFilm allows customized protocols to be created in a simple and straightforward manner to mimic key processes in thin-film formation. Simulations of vacuum deposition and solvent evaporation can be performed with a specific composition and at a target growth rate.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As a consequence, much of our atomic-level understanding of these materials is based on modeling. In particular, molecular dynamics simulations are increasingly being used to model the process of deposition and growth and to predict the morphology of the subsequent thin film. For example, simulations of the vacuum deposition of guest/host blends have been used to predict differences in porosity and charge-carrier pathways in organic semiconductor films as a function of composition, and to understand factors that drive the alignment of molecules at the solid–vapor interface. ,,, Simulations of vacuum deposition have also been used to provide an atomic-level interpretation of a range of experimental data including those derived from X-ray diffraction experiments . In each case, predicting the final morphology critically depends on appropriately modeling the interatomic interactions between the individual components, as well as the dynamic processes occurring at the interfaces between the substrate and the deposited material, and between the growing film and the vacuum.…”
Section: Introductionmentioning
confidence: 99%
“…1,2,5,6 Simulations of vacuum deposition have also been used to provide an atomic-level interpretation of a range of experimental data including those derived from X-ray diffraction experiments. 5 In each case, predicting the final morphology critically depends on appropriately modeling the interatomic interactions between the individual components, as well as the dynamic processes occurring at the interfaces between the substrate and the deposited material, and between the growing film and the vacuum.…”
Section: ■ Introductionmentioning
confidence: 99%